Social Exclusion in the Arts: The Dynamics of Social and Economic Mobility Across Three Decades of Undergraduate Arts Alumni in the United States. Issue 1 (March 2022) - Whitaker, Amy; Wolniak, Gregory C.
This chapter presents a broad interdisciplinary literature review linking artists' economic precarity and need for but resistance to entrepreneurial skills, alongside colonial histories, structural racism, and hierarchies of taste in arts organizations. These themes are complemented empirically by engaging data from the Strategic National Arts Alumni Project (SNAAP) to demonstrate indicators of attrition and privilege of arts alumni relative to their participation in the arts workforce. Meaningfully different associations across racial/ethnic groups are uncovered, showing structural exclusion of Black arts alumni in particular, in addition to other intersectional dynamics. This chapter underscores the importance of addressing student debt, the potential of creative pedagogies across the curriculum, and the need for imaginative approaches to renewed public funding of art and artists.